A novel U-bent plastic optical fibre local surface plasmon resonance sensor based on a graphene and silver nanoparticle hybrid structure - Jiang, Shouzhen; Li, Zhe; Zhang, Chao; Gao, Saisai; Li, Zhen; Qiu, Hengwei; Li, Chonghui; Yang, Cheng; Liu, Mei; Liu, Yanjun (Journal of physics. D, Applied physics, 2017)
In this work, we have presented a novel local surface plasmon resonance (LSPR) sensor based on the U-bent plastic optical fibre (U-POF). Firstly, a layer of discontinuous silver (Ag) thin film was deposited on the U-POF and then the Ag film was covered by a layer of cladding synthesized by polyvinyl alcohol (PVA), graphene and silver nanoparticles forming the PVA/G/AgNPs@Ag film. The normalized transmittance spectrum of the LSPR sensor have been collected in a range of the refractive index (RI) from 1.330 to 1.3657 in ethanol solution, and 700.3 nm/RIU sensitivity of the developed LSPR sensor has been demonstrated. By experiments, we demonstrated that the graphene could improve the sensitivity of the LSPR sensor and delay the oxidation process of the AgNPs effectively to keep the stability of the LSPR sensor. The LSPR sensor also exhibited good sensitivity and linearity in the detection of glucose solutions. This work shows that the developed LSPR sensor may have promising applications in biosensing.